Comparison of AlGaN/GaN MISHEMT powerbar designs. Issue 3 (7th February 2014) - Stoffels, Steve; Ronchi, Nicoló; Venegas, Rafael; De Jaeger, Brice; Marcon, Denis; Decoutere, Stefaan
Abstract: This works presents a comparison of several different AlGaN/GaN powerbar designs, with a total gate width of 9mm, with the goal to minimize the total gate resistance. Analytical models were developed for the interconnect parasitics to aid in the design phase. The different power transistor topologies were fabricated in a GaN‐on‐Si MISHEMT technology. Measurements on the fabricated transistors showed a good agreement between the analytical models and the measurements. Furthermore, the modelling framework allowed us to design power transistors that reached the goal of reducing the gate resistance while having minimal impact on other characteristics. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)